Reflecting trends of the contemporary academic landscape in the context of Higher Education 4.0 - Ülker, Nilüfer (Frontiers in Education, 2025)
The world has become a place where information can be accessed quickly and disseminated widely in the knowledge society in parallel with the speed of technological advancements. The shift of focus toward knowledge economy has necessitated the transformation of higher education institutions to meet the demands of the current era, as indicated by the commencement of the 4th industrial revolution, also referred to as Industry 4.0 (I4.0). Universities are now expected to equip their graduates with necessary competencies for the jobs of the future so that they will fulfill the professional demands and requirements of I4.0. To be able to achieve this, modifications have taken place in many spheres of higher education including but not limited to the adoption of new instructional methodologies, changes in the teaching and learning environment and the redefinition of student competencies in line with the requirements of the current era. In parallel with this approach, the aim of the European Universities Initiative (EUI) is to transform the quality and competitiveness of European higher education where the alliances are expected to become universities of the future with a specific focus on student-centered curricula and innovative teaching approaches. To this end, employing a comparative survey design, this study will explore perceptions of academics in a European University Alliance (EUA) concerning the extent to which already existing academic practices align with good practice indicators defined for Higher Education 4.0 (HE4.0). Data was collected from an EUA through a statistically valid and reliable scale devised by the researcher. In total, 161 academics from nine different European Universities participated in the research. Factor analysis, validity and reliability testing, and comparative statistical methods (Kruskal Wallis-H, Mann Whitney-U, One-Way ANOVA, Independent Samples T Tests, Pearson Correlation) were performed for data analysis. The findings indicate that female academics and academics actively involved in EUA activities demonstrate higher awareness of good practice indicators in the scope of HE4.0. Being actively involved in EUAs to mainstream good academic practice across higher education institutions will contribute to keeping up with the rapidly changing academic landscape in the 4th industrial era.